The Expression of Three Negative Co-Stimulatory B7 Family Molecules in Small Cell Lung Cancer and Their Effect on Prognosis - Qiu, Meng-jun; Xia, Qin; Chen, Yao-bing; Fang, Xie-fan; Li, Qiu-ting; Zhu, Li-sheng; Jiang, Xin; Xiong, Zhi-fan; Yang, Sheng-li (Frontiers in Oncology, 2021)
Background: In recent years, immune checkpoint inhibitors have shown significant effects in a variety of solid tumors. However, due to the low incidence of small cell lung cancer (SCLC) and its unclear mechanism, immune checkpoints in SCLC have not been fully studied. Methods: We evaluated the expression of PD-L1, B7-H3, and B7-H4 in 115 SCLC tissue specimens using immunohistochemistry. The clinical data of patients with SCLC were retrospectively reviewed to investigate three negative co-stimulatory B7 family molecules' ability to affect the prognosis of SCLC. Results: Among the SCLC patients with complete follow-up data (n = 107), sixty-nine (64.49%) expressed moderate to high B7-H3 levels, which correlated positively with tumor sizes (P < 0.001). Eighty (74.77%) patients expressed moderate to high B7-H4 levels, which correlated positively with metastases (P = 0.049). The positive expression of B7-H3 and B7-H4 correlated significantly with shortened overall survival (OS) (B7-H3, P = 0.006; B7-H4, P = 0.019). PD-L1 was positively expressed only in 13.08% of cancer tissues, and there was no significant correlation with prognosis. The Cox proportional hazards regression showed that B7-H3 was an independent prognostic indicator of OS (P = 0.028; HR = 2.125 [95% CI = 0.985-4.462]). Conclusions: Our results suggest that B7-H3 has a negative predictive effect on SCLC. This outcome provides a theoretical basis for the subsequent research on immune checkpoint inhibitors targeting B7-H3.